Mt. Erebus, the largest point source of NO2 in Antarctica - Oppenheimer, C; Kyle, P; Tsanev, V; McGonigle, A; Mather, T; Sweeney, D (2005)
We report here the first observations of NO2 emission from Mt. Erebus, a volcano with an active lava lake located on Ross Island, Antarctica. Erebus generates a persistent plume, which is entrained at an altitude of about 4 km above sea level. Its NO2 flux, measured by scattered light ultraviolet spectroscopy in December 2003, was equivalent to ∼0.6 Gg (N) yr-1. The total reactive nitrogen supply may be significantly higher than this since other NOy species are likely to have been present in the plume. We believe the NO2 is generated by thermal fixation of atmospheric nitrogen at the hot lava surface, forming NO, which then reacts rapidly with oxidants including ozone to yield NO2. Erebus volcano has displayed lava lake activity for many decades and may, therefore, play a significant long-term role in Antarctic tropospheric chemistry, and represent an important source of nitrogen deposited to the ice surface. © 2005 Elsevier Ltd. All rights reserved.